Income Disparities in the Use of Health Screening Services Among University Students in Korea: A Cross-Sectional Study of 2479 Participants in a University. Issue 20 (May 2016) - Lee, Su Hyun; Joh, Hee-Kyung; Kim, Soojin; Oh, Seung-Won; Lee, Cheol Min; Kwon, Hyuktae
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Public health insurance coverage for preventive care in young adults is incomplete in Korea. Few studies have focused on young adults' socioeconomic disparities in preventive care utilization. We aimed to explore household income disparities in the use of different types of health screening services among university students in Korea. This cross-sectional study used a web-based self-administered survey of students at a university in Korea from January to February 2013. To examine the associations between household income levels and health screening service use within the past 2 years, odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using logistic regression with adjustment for various covariables. Of 2479 participants, 45.5% reported using health screening services within 2 years (university-provided screening 32.9%, private sector screening 16.7%, and both 4.1%). Household income levels were not significantly associated with overall rates of health screening service use with a multivariable-adjusted OR (95% CI) in the lowest versus highest income group of 1.12 (0.87–1.45, P trend  = 0.35). However, we found significantly different associations in specific types of utilized screening services by household income levels. The multivariable-adjusted OR (95% CI) of university-provided health screening service use in the lowest versus highest income level was 1.74 (1.30–2.34; P trend  < 0.001), whereas the multivariable-adjusted OR (95% CI) of private sector service use in the lowest versus highest income level was 0.45 (0.31–0.66; P trend  < 0.001). This study demonstrated significant disparities in the types of utilized health screening services by income groups among university students in Korea, although overall rates of health screening service use were similar across income levels. Low-income students were more likely to use university-provided health screening services, and less likely to use private sector screening services. To ensure appropriate preventive care delivery for young adults and to address disparities in disadvantaged groups, the expansion of medical insurance coverage for preventive health care, establishment of a usual source of care, focusing on vulnerable groups, and the development of evidence-based standardized health screening guidelines for young adults are needed.